The designer's guide to the Cortex-M processor family - Martin, Trevor (Technical writer) (Newnes, 2022)
The Designer's Guide to the Cortex-M Microcontrollers, Third Edition provides an easy-to-understand introduction to the concepts required to develop programs in C with a Cortex-M based microcontroller. Sections cover architectural descriptions that are supported with practical examples, enabling readers to easily develop basic C programs to run on the Cortex-M0/M0+/M3 and M4 and M7 and examine advanced features of the Cortex architecture, such as memory protection, operating modes and dual stack operation. Final sections examine techniques for software testing and code reuse specific to Cortex-M microcontrollers. Users will learn the key differences between the Cortex-M0/M0+/M3 and M4 and M7; how to write C programs to run on Cortex-M based processors; how to make the best use of the CoreSight debug system; the Cortex-M operating modes and memory protection; advanced software techniques that can be used on Cortex-M microcontrollers, and much more. Includes an update to the latest version (5) of MDK-ARM, which introduces the concept of using software device packs and software components Includes overviews of new CMSIS specifications Covers developing software with CMSIS-RTOS, showing how to use RTOS in real- world design.